Exams or applications? Elite Taiwanese students' perceptions and navigation of college admissions systems. (April 2022) - Chiang, Yi-Lin
Studies often portray elite students as self-interested adolescents who justify educational selection systems that favor them. However, this perspective neglects critiques of the college admissions system on the part of the elite, who often have no other option than to support it as fulfilling the ideals of fairness. This study examines academic elite students' perceptions of college admissions systems when they are given choices as to which system to use. Data for this study come from surveys, interviews, and participant observation in Taiwan, where students are selected through two systems: exam-based selections and application-based selections. The findings show that students in elite high schools perceive whichever system that benefits them to be the fairest. By narrowly defining fairness as family influence on admission outcomes, these students downplay the institutional advantages they enjoy and present themselves as deserving candidates. Using the example of elite Taiwanese students, this study highlights that elites justify privilege based on self-interest and strategically navigate admissions systems to accrue advantages.